Leveraging persuasive communication: How the Beach Clean Up Bengkulu Community shapes environmentally friendly behavior at Panjang Beach - Iqbaal Suryahandika; Dhanurseto Hadiprashada; Dionni Ditya Perdana (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
This study aimed to analyze the persuasive communication of the Beach Clean Up Bengkulu Community in shaping the environmentally friendly behavior of the Panjang Beach community. Using a descriptive qualitative approach, data were obtained through in-depth interviews and documentation. Informants were purposively selected based on their experience, responsibilities, and duration of involvement in the community. This research offers a theoretical contribution by integrating the concepts of communicator credibility, persuasive messages, and media used by the Beach Clean Up Bengkulu Community in shaping environmentally friendly behavior in the Panjang beach community in Bengkulu City. The findings show that the #BesamoBersihkanPantaiKito campaign effectively combines communicator credibility, reflected by members' expertise and behavioral consistency, with persuasive communication strategies based on straightforward and educative verbal and nonverbal messages through visual symbols. The media used included offline media (creative posters and tumbler merchandise) and online media (Instagram), which provided a wider reach. The practical implication of the findings is that the persuasive communication model used can be adopted by other communities to organize environmental campaigns. The novelty of this research lies in the combination of the use of traditional and digital media aligned with the message strategy to build active community participation. This study provides important insights for developing more inclusive and effective environmental campaigns at local and global levels.   Penelitian ini bertujuan untuk menganalisis komunikasi persuasif Komunitas Beach Clean Up Bengkulu dalam membentuk perilaku ramah lingkungan masyarakat Pantai Panjang. Dengan pendekatan kualitatif deskriptif, data diperoleh melalui wawancara mendalam dan dokumentasi. Informan dipilih secara purposive berdasarkan pengalaman, tanggung jawab, dan lamanya keterlibatan mereka dalam komunitas. Penelitian ini menawarkan kontribusi teoritis dengan mengintegrasikan konsep kredibilitas komunikator, Pesan persuasif, dan media yang digunakan oleh Komunitas Beach Clean Up Bengkulu dalam membentuk perilaku ramah lingkungan pada masyarakat Pantai Panjang Kota Bengkulu. Temuan menunjukkan bahwa kampanye #BesamoBersihkanPantaiKito secara efektif menggabungkan kredibilitas komunikator, yang tercermin dari keahlian dan konsistensi perilaku anggota, dengan strategi komunikasi persuasif berbasis pesan verbal yang lugas dan edukatif serta pesan nonverbal melalui simbol visual. Media yang digunakan meliputi media offline (poster kreatif dan merchandise tumbler) dan media online (Instagram), yang memberikan jangkauan lebih luas. Implikasi praktis dari temuan ini adalah model komunikasi persuasif yang digunakan dapat diadopsi oleh komunitas lain dalam menyelenggarakan kampanye lingkungan. Kebaruan penelitian ini terletak pada kombinasi penggunaan media tradisional dan digital yang diselaraskan dengan strategi pesan untuk membangun partisipasi masyarakat secara aktif. Penelitian ini memberikan wawasan penting bagi pengembangan kampanye lingkungan yang lebih inklusif dan efektif di tingkat lokal maupun global.